Polymorphisms of glutathione S-transferase genes and survival of resected hepatocellular carcinoma patients - Qu, Kai (World journal of gastroenterology : WJG, 2015)
AIM: To investigate the effects of single nucleotide polymorphisms(SNPs) in glutathione S-transferase(GST) genes on survival of hepatocellular carcinoma(HCC) patients.METHODS: Twelve tagging SNPs in GST genes(including GSTA1, GSTA4, GSTM2, GSTM3, GSTO1, GSTO2 and GSTP1) were genotyped using Sequenom Mass ARRAY i PLEX genotyping method in a cohort of 214 Chinese patients with resected HCC.The Cox proportional hazards model and log-rank test were performed to determine the SNPs related to outcome.Additionally, stratified analysis was performed at each level of the demographic and clinical variables.An SNP-gene expression association model was further established to investigate the correlation between SNP and gene expression.RESULTS: Two SNPs(GSTO2 : rs7085725 and GSTP1 : rs4147581) were significantly associated with overall survival in HCC patients(P = 0.035 and 0.042, respectively).In stratified analysis, they were more significantly associated with overall survival in patients with younger age, male gender and cirrhosis.We further investigated cumulative effects of these two SNPs on overall survival in HCC patients.Compared with the patients carrying no unfavorable genotypes, those carrying 2 unfavorable genotypes had a 1.70-fold increased risk of death(P < 0.001).The cumulative effects were more significant in those patients with younger age, male gender and cirrhosis(HR = 2.00, 1.94 and 1.97, respectively; all P < 0.001).Additionally, we found that heavy smoking resulted in a significantly worse overall survival in those patients carrying variantalleles of rs7085725(HR = 2.07, 95%CI: 1.13-3.76, P = 0.018).The distributions of GSTO2 : rs7085725 and GSTP1 : rs4147581 genotypes were associated with altered gene expression and contributed to influences on overall survival.CONCLUSION: Our study provides the first evidence that GSTO2 and GSTP1 gene polymorphisms may serve as independent prognostic markers for HCC patients.